(untitled) (American International Journal of Economics and Finance Research, 2020)
This study investigated the relationship between macroeconomic variables and the performance of deposit money banks in Nigeria, analyzed with suitable finametric tools. The results of the empirical examination found that all the macroeconomic variables employed (economic growth rate, interest rate, inflation rate, money supply and exchange rate in this study have no significant relationship with bank performance. It was also observed that each and jointly, the macroeconomic variables do not cause bank performance both in the short run and long run. Again, that bank performance responds insignificantly to the shocks of all the macroeconomic variables. Consequently the researchers advocate that deposit money banks in Nigeria with inherent discretionary policy be proactive to the monetary and fiscal policies of regulatory authorities in order to enhance their performance.